2007
DOI: 10.1007/s00125-007-0609-0
|View full text |Cite
|
Sign up to set email alerts
|

Global profiling of genes modified by endoplasmic reticulum stress in pancreatic beta cells reveals the early degradation of insulin mRNAs

Abstract: Aims/hypothesis Pancreatic beta cells respond to endoplasmic reticulum (ER) stress by activating the unfolded protein response. If the stress is prolonged, or the adaptive response fails, apoptosis is triggered. We used a 'homemade' microarray specifically designed for the study of beta cell apoptosis (the APOCHIP) to uncover mechanisms regulating beta cell responses to ER stress. Materials and methods A time course viability and microarray analysis was performed in insulin-producing INS-1E cells exposed to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
78
2
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(91 citation statements)
references
References 51 publications
9
78
2
2
Order By: Relevance
“…In other cell types, activation of the IRE1α-XBP1s pathway increases production of ERproteins aiming to fold and/or degrade misfolded proteins. Together with previous studies [27,46], our data suggest that the IRE1α-XBP1s pathway has a distinct role in beta cells, relative to the fine-tuning of insulin mRNA expression through transcriptional and post-transcriptional mechanisms, allowing for rapid adjustment of insulin levels under ER-stress conditions [46]. However, due to the deleterious effects of prolonged increased XBP1s level, this mechanism has to be closely regulated in beta cells, resulting in a limited XPB1 splicing as shown by previous studies [2,12] and the present data.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…In other cell types, activation of the IRE1α-XBP1s pathway increases production of ERproteins aiming to fold and/or degrade misfolded proteins. Together with previous studies [27,46], our data suggest that the IRE1α-XBP1s pathway has a distinct role in beta cells, relative to the fine-tuning of insulin mRNA expression through transcriptional and post-transcriptional mechanisms, allowing for rapid adjustment of insulin levels under ER-stress conditions [46]. However, due to the deleterious effects of prolonged increased XBP1s level, this mechanism has to be closely regulated in beta cells, resulting in a limited XPB1 splicing as shown by previous studies [2,12] and the present data.…”
Section: Discussionsupporting
confidence: 77%
“…We and others have previously shown that the IRE1α-XBP1s pathway of the UPR controls insulin expression, mainly through IRE1α-mediated degradation of insulin mRNA [27,45,46]. In the present study we demonstrate another level of regulation of insulin expression by the UPR, via XBP1s-dependent downregulation of Pdx1 and Mafa.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations